Modern Technologies for Resolving Conflicts Within an Organization (Laisvalaikio tyrimai, 2022)
Research problem and degree of the research: Today, conflicts take place in all organizations. Current realities do not allow enterprises to exist in a comfort zone without internal obstacles; otherwise, an institution simply will not survive. This article is based on both the positive meaning of conflict and on an analysis of the negative aspects of conflict, specifically regarding modern technologies which allow resolving conflict contradictions in some cases or to avoid it completely in others, for example, when there are rudiments of their maturation.Purpose of the article: to analyze modern technologies for resolving conflicts in an organization.Subject of the article:  Modern technologies for conflict resolution.There are quite a few types of intra-organizational conflicts, but we will focus on the contradictions that arise in teams. The article analyzes the technologies of conflict resolution in two projections: in resolving a conflict that has already arisen and in its prevention.Research methods: The following research methods were used:⎯ theoretical analysis of scientific sources;⎯ analysis of foreign conflict resolution techniques.Modern conflict resolution technologies are focused on the constructive participation of all parties to the conflict. At the same time, the managers’ actions play a certain role, as they are endowed with exclusive functions for managing conflicts within their department and they are personally responsible for the situation in the team.Of course, it is necessary to apply preventive methods to prevent contradictions. If nevertheless the conflict emerged for various reasons: either the contradiction was implicit, or this issue was not given due attention, it is necessary to be guided by slightly different methods. In any case, the resolution of intra-organizational conflicts in a team should be focused on the psychological aspect of employees. It is necessary to work with each employee, paying attention to his or her needs and interests.Conclusion. This article examined the main modern methods for preventing and resolving conflicts, used in many organizations. The theoretical aspects of intra-organizational conflicts, including the cause of the conflict, its’ structure and typology were considered.  The article was also focused on the typical managers’ mistakes when resolving conflicts.Key words:  corporate conflict, resolution technologies, managerial impact, mediation.